Enzymatic Cellulose Palmitate Synthesis Using Immobilized Lipase - Anna Roosdiana; Diah Mardiana; Ellya Indahyanti; Dyah Ayu Oktavianie (Research Journal of Life Science, 2017)
Bacterial cellulose can be modified by esterification using palmitic acid and Mucor miehei  lipase  as catalyst. The purpose of this research was to determine the optimum conditions of esterification reaction of cellulose and palmitic acid . The esterification reaction was carried out at the time variation  of  6, 12, 18, 24 and 30 hours and the mass ratio of cellulose: palmitic acid (1: 11: 2, 1: 3, 1: 4, 1: 5,1:6) at 50 °C. The   cellulose palmitate  was examined  its  physical and chemical properties by using FTIR spectrophotometer, XRD, bubble point test and saponification  apparatus. The results showed that the optimum reaction time of esterification reaction of cellulose and palmitic acid occurred within 24 hours and the mass ratio of cellulose: palmitic acid was 1: 3 resulting in DS of  0.376 with  swelling index of 187 %, crystallinity index of 61.95%,  and Φ porous of 2.40 μm. Identification of functional groups using FTIR spectrophotometer showed that C=O ester group  was observed at 1737.74 cm-1 and strengthened  by  the appearance of C-O ester peak at 1280 cm-1. The conclusion of this study is reaction time and reactant ratio influence significantly the DS of cellulose ester.